A Fair Value Hierarchy and Corporate Governance Mechanisms in Financial Institutions - nuryani, nunung (Adpebi Science Series, 2024)
The International Accounting Standard Board (IASB) has issued IFRS 13 regarding fair value measurement in a hierarchy. The fair value measurement in the hierarchy at level 3 for unobservable prices involves the largest estimate so that fair value information at level 3 is less reliable and less relevant in the company's valuation. Therefore, this study aims to re-examine whether fair value measurements at level 1 and level 2 are more relevant than at level 3, and whether corporate governance can strengthen the relevance of fair value information at level 3. By using a sample of 55 companies in financial institutions, the results of this study indicate that the fair value information of assets and liabilities at level 1 and 2 does not prove to be more relevant than the fair value information at level 3. In addition, corporate governance mechanisms, namely the number of independent commissioners and audit committee expertise, can strengthen the value relevance of assets and liabilities fair value information at level 3